2014
DOI: 10.1007/s10096-014-2269-6
|View full text |Cite
|
Sign up to set email alerts
|

Prior statin use and 90-day mortality in Gram-negative and Gram-positive bloodstream infection: a prospective observational study

Abstract: In several studies on patients with bloodstream infection (BSI), prior use of statins has been associated with improved survival. Gram-positive and Gram-negative bacteria alert the innate immune system in different ways. We, therefore, studied whether the relation between prior statin use and 90-day total mortality differed between Gram-positive and Gram-negative BSI. We conducted a prospective observational cohort study of 1,408 adults with BSI admitted to Levanger Hospital between January 1, 2002, and Decemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 35 publications
(42 reference statements)
0
16
1
Order By: Relevance
“…Of particular note is that the majority of the studies reviewed so far did not adjust for the type of statin used or the type of bacteria causing the infection. An interesting study of the effect of prior statin use on mortality in patients with bloodstream infections found a significant reduction in 90-day mortality in statin users with Gram-negative infections (adjusted OR, 0.38; 95% CI, 0.20 to 0.72; P ϭ 0.003) but no significant difference in statin users with Gram-positive infections (adjusted OR, 1.22; 95% CI, 0.69 to 2.17; P ϭ 0.49) (36), suggesting that the type of bacterial infection may be a significant factor.…”
Section: Clinical Evidence That Statins Influence Morbidity and Mortamentioning
confidence: 97%
“…Of particular note is that the majority of the studies reviewed so far did not adjust for the type of statin used or the type of bacteria causing the infection. An interesting study of the effect of prior statin use on mortality in patients with bloodstream infections found a significant reduction in 90-day mortality in statin users with Gram-negative infections (adjusted OR, 0.38; 95% CI, 0.20 to 0.72; P ϭ 0.003) but no significant difference in statin users with Gram-positive infections (adjusted OR, 1.22; 95% CI, 0.69 to 2.17; P ϭ 0.49) (36), suggesting that the type of bacterial infection may be a significant factor.…”
Section: Clinical Evidence That Statins Influence Morbidity and Mortamentioning
confidence: 97%
“…Case fatality rate was measured as all-cause mortality within day 30 and 90. By using the 11-digit unique identification number of all Norwegian citizens, electronic hospital records in Norway are updated with mortality data from the Norwegian population registry so that mortality data after discharge from hospital can be reliably assessed [ 21 , 22 ].…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…Since 1994 the Mid-Norway Sepsis Study has continuously prospectively registered patients with confirmed BSI identified by growth of one or more microbes from blood culture, combined with clinical evidence of systemic infection [ 8 ]. A new occurrence of BSI was recorded for patients if at least 30 days had passed since a previous incident [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…A new occurrence of BSI was recorded for patients if at least 30 days had passed since a previous incident [ 9 ]. Clinical information from the patients’ records was recorded retrospectively, after standardized definitions, by a team of trained health care professionals for all patients admitted before 2014 [ 8 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation